Tobacco-related morbidity and nicotine dependence: An experience in an urban slum of Burdwan district, West Bengal, India - Indranil Saha; Kamirul Islam; Bobby Paul; Tapas Kumar Som (Wolters Kluwer Medknow Publications, 2018)
Tobacco use causes many diseases irrespective of age and sex. More the addiction, more is the occurrence of morbidity in terms of frequency and severity. This community-based study was conducted to find out any relationship between the morbidity associated with tobacco use and nicotine dependence. In an urban slum - Alamganj, district Burdwan, West Bengal, India, from January to October 2012 among 128 current adult tobacco users using Fagerström test for nicotine dependence (FTND) questionnaire. Tobacco users were maximally suffering from chronic obstructive pulmonary disease (COPD) (27.27%), gastritis (25.45%), and leukoplakia (25.45%). For individual diseases, the difference in FTND score was significantly high in cases of gastritis, hypertension, and COPDs. All types of morbidity were more common in the group of high nicotine dependence. FTND score can be suitably used to assess nicotine dependence of the tobacco users, who can be counseled accordingly to reduce the tobacco-related morbidity and mortality.